Theory of Phase Transition in Rare Earth Chalcogenide Compounds - Adhikari, D.R.; Subedi, D.P.; Singh, V.K. (Kathmandu University Journal of Science Engineering and Technology, 2006)
In a number of rare earth chalcogenide compounds [(SmX, YbX, EuX)] where X=S, Se and Te], the atomic-like f levels and the wide s-d band co-exist at the Fermi level. Such compounds are considered mixed -valence compounds and ionic semiconductor at atmospheric pressure.